Komik Edukasi sebagai Media Guru Sekolah Dasar dalam Pembelajaran Masalah Sosial Kritis di Dunia Digital - Naufan Noordyanto; Yurif Setya Darmawan; Tedi Mursalat Farqo; Yurid Eka Nugraha; Maulana Yafie Danendra; Avivi Marhamah (Sewagati, 2026)
The acceleration of digitalization in the education sector presents both opportunities and challenges, particularly the emergence of critical social issues in the digital environment that affect elementary school students. Teachers, as key actors in character education, still face limitations in digital literacy competencies and the availability of contextual learning media to address these issues effectively. In response, this community service program aimed to strengthen elementary teachers’ digital literacy through the use of educational comics. A case study approach with a pilot project was implemented in collaboration with the Teachers’ Working Group (KKG) 02 in Guluk-Guluk District, Sumenep Regency. The program involved stages of data collection, problem analysis, development of five educational comic titles, classroom trials, and dissemination through teacher training. The results indicate that educational comics effectively increase students’ reading interest and assist teachers in explaining complex digital literacy issues, including online gambling prevention, hate speech, personal data protection, ethical promotion of local products, and cultural appreciation. Furthermore, teachers’ pedagogical capacity and confidence in integrating digital literacy into classroom instruction improved significantly. These findings highlight that educational comics serve as relevant and inclusive instructional media with the potential to bridge the digital literacy gap between urban and rural elementary schools.